Karakteristik Papan Partikel Limbah Kayu Mahoni dengan Perlakuan Pengawetan Asap Cair - Agus Ngadianto; Ragil Widyorini; Ganis Lukmandaru (Penelitian dan Pengabdian Kepada Masyarakat Sekolah Vokasi Universitas Gadjah Mada, 2017)
This research focused on the characteristics of particleboard made from preservation treated-particl es. Mahagony wood bioma ss waste was used as raw material. Liquid smoke at different concentrations (0%, 2.5%, and 5%) was applied for 24hours onto the particles. After dried in air dry condition, the particles were mixed with urea formaldehyde resin (7.5% and15%), and then were pressed using hot pressing system at 150oC for 10 minutes. The result showed that the particleboardusing 15% urea formaldehyde resin and made form 5% liquid smoke treated-particles provided the best performance, thatmet Japanese Industry Standard (JIS) A 5908. The mortality value of dry wood termites Cryptotermes cynocephalus Lightand the weight loss after termite attack at the same condition were 90.67% and 0.408%, respectively.